2015
DOI: 10.1111/jam.12903
|View full text |Cite
|
Sign up to set email alerts
|

RpA, an extracellular protease similar to the metalloprotease of serralysin family, is required for pathogenicity of Ralstonia pickettii

Abstract: An extracellular protease, RpA, was identified from R. pickettii WP1 isolated from water supply system. The RpA metalloproteases is required for the pathogenicity of R. pickettii to mammalian cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…In addition, the pathogenesis of S. marcescens was also incited by other virulence enzymes such as serralysin protease and triacylglycerol lipase, which actively degrades serum proteins and interferes with host granulocyte function, respectively to elude the host defence system (Wei and Lai ; Chen et al . ). Similar to prodigiosin, VzAgNPs also inhibited virulence enzymes production of S. marcescens in a concentration‐dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the pathogenesis of S. marcescens was also incited by other virulence enzymes such as serralysin protease and triacylglycerol lipase, which actively degrades serum proteins and interferes with host granulocyte function, respectively to elude the host defence system (Wei and Lai ; Chen et al . ). Similar to prodigiosin, VzAgNPs also inhibited virulence enzymes production of S. marcescens in a concentration‐dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that Bacillus anthracis zinc-metalloprotease breaks down fibronectin, laminin and collagen; Pseodomonoas aerogenosa zinc-metalloprotease cleave fibrinogen elastin, laminin, α1-proteinase inhibitors, coagulation factors XII, IgA and IgG (Barrett et al, 2004;Chung et al, 2006); Proteus mirabilis produce zinc-metalloprotease that cleave IgA and IgG (Wassif et al, 1995); Staphylococcus epidermidis zincmetalloproteases degrades elastin, collagen, IgG and serum α l-protease inhibitor (Teufel and Gotz, 1993); Streptococcus pneumonia extracellular zinc-metalloprotease removes the membrane from the epithelial glycocalyx (Govindarajan et al, 2012); Vibrio cholera zinc-metalloprotease degrades the extracellular matrix components fibronectin, fibrinogen and plasminogen (Vaitkevicius et al, 2008;Edwin et al, 2014). Extracellular zincmetalloprotease is, also, characterized as toxin during Bacteroides fragilis, Ralstonia picketti and Serratia marcescens virulence (Marty et al, 2002;Wu et al, 2002;Chen et al, 2015), and is required for maturation of the pathogenic factor, phospholipase C (lecithinase), in Listeria monocytogenes (Coffey et al, 2000). Consequently, we do not exclude the possibility that proteolytic enzyme from Streptomyces P.B.373 is a pathogenic determinant.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, Mep active centers contain one or two metal ions, most of which are zinc-containing proteins. In fact, many zinc-containing bacterial proteases and fungal proteases are found throughout the world within microorganisms (Chen et al 2015;Ishii et al 2014;Wu et al 2011;Li et al 2014), such as the AprX extracellular metalloproteinases of many fluorescent pseudomonads (Dufour et al 2008;Zhang et al 2009), members of the Bacillus neutral protease family (Wu et al 2011) the SmP metalloprotease (serralysin) of Serratia marcescens (Chen et al 2015), the RpA metalloprotease (serralysin) of Ralstonia pickettii and alkaline protease of fungi . Extracellular Meps are known to be important virulence factors related to bacterial and fungal pathogenicity (Zhang et al 2017).…”
Section: Fig3mentioning
confidence: 99%